POTENSI DAN KESESUAIAN LAHAN RAWA UNTUK PENGEMBANGAN TANAMAN PADI DI KABUPATEN TOLITOLI SULAWESI TENGAH - Syafruddin Syafruddin (Universitas Tadulako, 2012)
The conversion of fertile rice land in some areas of rice production center has implications for food security achievement and farmers’ income. This problem has been anticipated by government through creating new rice field in potential land including swamp areas. The research objective was to identify the potency, suitability and opportunity of the swamp areas for rice farming system in Tolitoli regency Central Sulawesi. The research was conducted in two stages: 1) Preparation and 2) Field and laboratory research. Three soil orders were found in the research areas including Histosols with sub groups ranged from typic sulfihemist to typic sulfibrist, Entisols with sub group sulfit endoaquent, and Inceptisols with sub groups typic endoaquepts and sulfit endoaquepts. The potency for rice plant development was quite good. The land suitability class for rice plant in Lampasio was Moderately Suitable (S2) with nutrient retention (nr) and oxygen availability were its limiting factor. Marginally Suitable class (S3) occupied parts of Buga and Lampasio with dominant limiting factors were flood hazard, sulfide, and nutrient retention. The land suitability class of Not Suitable could also be found in both Lampasio and Bunga.